Human Immunodeficiency Virus Type 1 Two-Long Terminal Repeat Circles: A Subject for Debate - Olivares, Isabel; Pernas, María; Casado, Concepción; López-Galindez, Cecilio (AIDS reviews, 2016)
HIV-1 infections are characterized by the integration of the reverse transcribed genomic RNA into the host chromosomes making up the provirus. In addition to the integrated proviral DNA, there are other forms of linear and circular unintegrated viral DNA in HIV-1-infected cells. One of these forms, known as two-long terminal repeat circles, has been extensively studied and characterized both in in vitro infected cells and in cells from patients. Detection of two-long terminal repeat circles has been proposed as a marker of antiretroviral treatment efficacy or ongoing replication in patients with undetectable viral load. But not all authors agree with this use because of the uncertainty about the lifespan of the two-long terminal repeat circles. We review the major studies estimating the half-life of the two-long terminal repeat circles as well as those proposing its detection as a marker of ongoing replication or therapeutic efficacy. We also review the characteristic of these circular forms and the difficulties in its detection and quantification. The variety of approaches and methods used in the two-long terminal repeat quantification as well as the low reliability of some methods make the comparison between results difficult. We conclude that it is not possible to draw a clear supposition about the lifespan of two-long terminal repeat circles and consequently they should not be used as a marker of ongoing replication without a careful analysis of the methods and results.